2022
DOI: 10.1111/jcmm.17135
|View full text |Cite
|
Sign up to set email alerts
|

miR‐126‐5p enhances radiosensitivity of lung adenocarcinoma cells by inhibiting EZH2 via the KLF2/BIRC axis

Abstract: Radiotherapy is a common method for the treatment of lung adenocarcinoma, but it often fails due to the relative non‐susceptibility of lung adenocarcinoma cells to radiation. We aimed to discuss the related mechanisms by which miR‐126‐5p might mediate radiosensitivity of lung adenocarcinoma cells. The binding affinity between miR‐126‐5p and EZH2 and between KLF2 and BIRC5 was identified using multiple assays. A549 and H1650 cells treated with X‐ray were transfected with miR‐126‐5p mimic/inhibitor, oe‐EZH2, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Wang et al clarified that miR‐218 promoted apoptosis of U2OS osteosarcoma cells by targeting BIRC5 32 . In addition, it has been reported that BIRC5 was the direct target of KLF2 and miR‐126‐5p could promote KLF2 expression to inhibit BIRC5 activation in lung adenocarcinoma cells 33 . In the current study, the potential binding site of KLF2 on the BIRC5 promoter region was identified and verified through ChIP analysis and dual‐luciferase reporter analysis.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Wang et al clarified that miR‐218 promoted apoptosis of U2OS osteosarcoma cells by targeting BIRC5 32 . In addition, it has been reported that BIRC5 was the direct target of KLF2 and miR‐126‐5p could promote KLF2 expression to inhibit BIRC5 activation in lung adenocarcinoma cells 33 . In the current study, the potential binding site of KLF2 on the BIRC5 promoter region was identified and verified through ChIP analysis and dual‐luciferase reporter analysis.…”
Section: Discussionmentioning
confidence: 57%
“…32 In addition, it has been reported that BIRC5 was the direct target of KLF2 and miR‐126‐5p could promote KLF2 expression to inhibit BIRC5 activation in lung adenocarcinoma cells. 33 In the current study, the potential binding site of KLF2 on the BIRC5 promoter region was identified and verified through ChIP analysis and dual‐luciferase reporter analysis. The results indicate that KLF2 could suppress BIRC5 expression transcriptionally.…”
Section: Discussionmentioning
confidence: 78%
“…We may speculate that IgG and IgM participate in humoral immunity, CD4 + is involved in regulating or assisting immune response, CD8 + can inhibit and kill T-lymphocytes. [23][24][25] EGFR-TKI targeted therapy only mildly affects the reproduction of normal tissue cells, and will not cause damage to normal tissues. Therefore, it has a small impact on the immune function of the body.…”
Section: Discussionmentioning
confidence: 99%
“…23 MiR-126-5p represses cell migration and facilitates apoptosis to enhance the radiosensitivity of LUAD cells through modulating the enhancer of zeste two polycomb repressive complex two subunit (EZH2)/Krüppel-like factor 2 (KLF2)/baculoviral IAP repeat containing 5 (BIRC5) axis. 24 Our bioinformatics analysis showed that miR-587 was sponged by A2M-AS1 and targeted by bone morphogenetic protein 3 (BMP3). Notably, miR-587 was previously discovered to be upregulated in NSCLC samples and closely linked to tumor staging, and miR-587 ehnanced the proliferative and migratory capabilities of NSCLC cells by downregulating cylindromatosis (CYLD).…”
Section: Introductionmentioning
confidence: 99%